Mergers and Acquisitions in the Markets for Diagnostic Services: Evidence from the Finnish Private Health Care Sector - Mikko Nurminen (Aboa Centre for Economics (ACE), 2021)
Health care markets in developed countries have become increasingly concentrated, while at the same time there has been an increasing trend of mergers and acquisitions (M&As) in these markets. I study the impact of M&As in the diagnostic procedure market, a market that is an important part of the health care industry and patient care, but has received little attention in this context. I use detailed nationwide register data from the Finnish private health care sector. My difference-in-difference estimates show that M&As increased prices in blood tests in both the acquiring and acquired units, but not in X-rays and MRIs. I additionally estimate a patient demand model that reveals that prices have little impact on the choice of provider while the referring physician's influence is large, potentially contributing to the firms' ability to increase their price margins.
Keywords: L11; I11; J21; K21; 330; Diagnostic Services; Mergers and Acquisitions; Market Power; Private Health Care